Сценарии возникновения аварийных ситуаций на шламохранилищах и очистных сооружениях Республики Беларусь - Levkevich Виктор; Mikanovich Дмитрий; Vrublevskiy Андрей (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2013)
The analysis of methods is presented according to risk estimation of emergencies origin on hydraulic facilities on slime storages. Primary reasons of emergencies origin are assigned (depressurization of equipment and pipelines, flow over the dam crest, occurrence of filtration in the body of dams followed by its destruction.). The scenarios of possible accidents on slime storages and treatment facilities are presented.